A pilot placebo-controlled, double-blind, and randomized study on the cognition-enhancing benefits of a proprietary chicken meat ingredient in healthy subjects - Md. Zain, Azhar; Jamil @ Osman, Zubaidah; Naing, Khin Ohnmar@ Noorjan; Zhuang, Candy Yi Jing; Tsang, Fai (BioMed Central, 2013)
Background: It has long been postulated that the relative abundance of specific nutrients can affect cognitive processes and emotions. Newly described influences of dietary factors on neuronal function and synaptic plasticity have revealed some of the vital mechanisms that could be responsible for the action of diet on brain health and cognitive function. Here, through a double-blind, randomized, placebo-controlled trial, we asked if the newly discovered chicken meat ingredient-168 (CMI-168) could be beneficial to the cognitive function in healthy adults.